Software Architecture of E-assessment on Higher Education - Wardani Muhamad; Wawa Wikusna (IJAIT (International Journal of Applied Information Technology), 2017)
Computer technology has been used to support the learning process at the university. Learning process, generally involved students and teachers in order to learn about materials on subject courses and also evaluate student competencies regularly. Teachers can evaluate student competencies or knowledge by e-assessment. E-assessment is one of the domains of e-learning which involves the use computer in assessment, includes: setting, delivery, marking and reporting of assessments. The Major benefit of the e - assessment system is its flexibility in term of global access and devices used to access. When developing an e-assessment system, we have two focuses on multi-dimensional approach, such as user friendly and student centric nature. Because of its complexity, software architecture need to define so software developer will develop software properly. By designing software architecture, view of the system that includes the system components, the behavior of those components, and the ways the components interact could clearly define. Architecture Description Language (ADL) has been used to describe software, because it provides a concrete syntax and formal framework for characterizing architectures. As the result, the design of e-assessment system architecture can meet the needs of attribute quality. The use of notation to explain ADL is able to provide a complete description than simply explaining ADL is using text. Furthermore, the e-assessment system architecture design is expected to be used as a reference for software development in establishing an e-assessment system.